2020
DOI: 10.1001/jamaophthalmol.2020.2289
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Ocular Surface State of Ophthalmologists and Ophthalmic Nurses Working With Patients With Coronavirus Disease 2019

Abstract: IMPORTANCE The influence on the psychology and ocular surface of ophthalmologists and ophthalmic nurses in Wuhan, China, during the coronavirus disease 2019 (COVID-19) pandemic is not yet fully understood. OBJECTIVE To characterize mental state and ocular surface state of ophthalmologists and ophthalmic nurses in Wuhan, China, and similar areas during the COVID-19 outbreak. DESIGN, SETTING, AND PARTICIPANTS This survey study assessed ophthalmologists and ophthalmic nurses in Wuhan, China, and Jiangxi, China, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…Moreover, depression could affect sleep quality, social function and energy levels which could lead to a low quality of life ( Malhi and Mann, 2018 ). As expected, we found that OD nurses with depression reported lower QOL than those without depression, which is similar to the previous findings ( Malhi and Mann, 2018 ; Shao and Zhang, 2020 ; Sjöberg et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, depression could affect sleep quality, social function and energy levels which could lead to a low quality of life ( Malhi and Mann, 2018 ). As expected, we found that OD nurses with depression reported lower QOL than those without depression, which is similar to the previous findings ( Malhi and Mann, 2018 ; Shao and Zhang, 2020 ; Sjöberg et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety ( n = 103), depression ( n = 73), stress ( n = 68), fear ( n = 61), burnout ( n = 25), mental distress/health ( n = 21), and post-traumatic stress disorder (PTSD) ( n = 14) (Additional File 3 ). Most COVID-19 studies reported on physicians from USA ( n = 23) [ 41 , 52 , 66 , 70 , 77 , 90 – 107 ], China ( n = 22) [ 15 , 49 , 54 56 , 65 , 68 , 73 , 86 , 89 , 102 , 108 118 ] followed by India ( n = 21) [ 40 , 50 , 58 , 63 , 67 , 71 , 102 , 119 – 132 ] [ 41 , 52 , 66 , 70 , 77 ], Italy ( n = 10) [ 32 , 94 , 102 , 125 , 133 138 ], and Turkey ( n = 11) [ 35 , 44 , 94 , 139 – 146 ] [ 28 , 30 , 32 , 34 , 36 , 37 , 42 , 45 , 47 , 48 , 59 , 60 , 62 , 80 , 87 ]. .Sixtee...…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety was frequently associated with depression and stress [88][89][90][91][92], sharing some of its determinants. Anxiety and depression were commonly either the result or the drivers for burnout, stress, distress and PTSD and poor well-being [31,65,[93][94][95][96][97].…”
Section: Anxietymentioning
confidence: 99%